Toward a Greater Understanding of the Willingness to Request an Accommodation: Can Requesters' Beliefs Disable the Americans with Disabilities Act? - Baldridge, David; Veiga, John F. (Academy of Management Review, 2001)
David C. Baldridge, John F. Veiga, Toward a Greater Understanding of the Willingness to Request an Accommodation: Can Requesters' Beliefs Disable the Americans with Disabilities Act?, The Academy of Management Review, Vol. 26, No. 1 (Jan., 2001), pp. 85-99